Donald Sultan - The disaster paintings - Hearst, Alison (DelMonico Books, Prestel, 2016)
A critically important series in the oeuvre of American painter, sculptor, and printmaker Donald Sultan, The Disaster Paintings were created between 1984 and 1990. These works feature imposing, man-made structures, whose industrial qualities are reinforced by Sultan’s preferred media, Masonite tiles and tar. The paintings’ resulting sense of robust permanence is offset by the catastrophes Sultan includes therein, which provoke a jarring sense of fragility, impermanence, and transience. Such unexpected juxtapositions are privileged by the artist’s process itself, which merges the industrial materials of Minimalism with representational painting, stylistically combining figuration and abstraction and making simultaneous reference to high and low culture. Painted on a large scale (the majority of the works in this series measure 8’ x 8’), The Disaster Paintings embody great physicality in their process, subject matter, and finished form. They also reify the modern experience of industrialized societies with images of fire, accidents, and industrial mishaps, daring us to forget that calamities and adversity are woven into the very fabric of our existence. It is a timely moment in history to reconsider and reassess The Disaster Paintings. - Published to accompany the exhibition of the same name held at Lowe Art Museum, Coral Gables, Florida, 20th September-23rd December 2016; Modern Art Museum of Fort Worth, Texas, February-April 2017; and the Smithsonian American Art Museum, Washington, DC, May-September 2017
Keywords: Sultan, Donald -- 1951-; Ausstellungskatalog -- Lowe Art Museum -- 19.02.2017-23.04.2017 -- Miami, Fla.; Ausstellungskatalog -- Modern Art Museum of Fort Worth -- 19.02.2017-23.04.2017 -- Fort Worth, Tex.; Ausstellungskatalog -- Smithsonian American Art Museum -- 26.05.2017-04.09.2017 -- Washington, DC; Ausstellungskatalog -- North Carolina Museum of Art -- 23.09.2017-31.12.2017 -- Raleigh, NC; Ausstellungskatalog -- Sheldon Museum of Art -- 24.01.2018-13.05.2018 -- Lincoln, Neb.